The influence of cognitive control on the processing of L2 garden path sentence among Chinese–English bilinguals - Xie, Zhilong; Zeng, Guofang; Zhou, Shuya; Wang, Juan (Frontiers in Behavioral Neuroscience, 2022)
Few studies have examined the role of cognitive control in processing ambiguity, let alone the roles of different components of cognitive control. In the current study, the English (L2) Sentence Processing Task and a series of cognitive control tasks were administered among 111 young adult Chinese-English bilinguals to investigate the influence of different components of cognitive control on garden path sentence comprehension, with other factors such as age, SES, and language proficiency strictly matched. Data analysis results showed a significant garden path effect on RTs and accuracy among all the participants. The results of independent t-test analyses revealed that the high WM group was faster in ambiguity resolution, and so was the high monitoring group. However, there were no differences between the high and low inhibition and shifting groups in ambiguity resolution. These findings reveal that only certain aspects of cognitive control influence garden path sentence comprehension.